ANALISIS PEMBOROSAN PRODUKSI KAIN PANEL MELALUI PENDEKATAN LEAN SUPPLY CHAIN - Marsella; Kosasih, Wilson; Salomon, Lithrone Laricha (Universitas Tarumanagara, 2025)
This study assesses the efficiency of a panel fabric production line at a Bekasi textile company using a Lean Supply Chain approach. Selected for its highest defect rate (62,919 defects from October 2024 to March 2025), 14 machines, and longest cycle time (14 days per batch), the line’s efficiency, dominant wastes, and improvement opportunities were examined. A descriptive single-case design gathered data through in-depth interviews, focus groups, and a seven-waste questionnaire. Process analysis began with Current Value Stream Mapping (VSM), followed by Value Stream Analysis Tools (VALSAT) via Process Activity Mapping (PAM) and Process Cycle Efficiency (PCE) calculations, then a 5 Whys analysis. PAM results indicated a PCE of 34.33%. The 5 Whys identified three root causes of waste: (1) lack of standardization and visual management, (2) unintegrated information flow, and (3) limited human-resource and equipment capacity. Key wastes included excess motion, inefficient material transport, inventory buildup, and waiting time. Recommendations include implementing 5S for workplace standardization, digitizing production with a pull system, and applying heijunka, kanban, and balanced flow to level production. Scheduled machine maintenance is advised to reduce defects. Adopting Hoshin Kanri and Future VSM will support continuous improvement and strategic alignment. These measures aim to reduce waste, boost productivity, sustain competitiveness, and foster sustainable business.